INFLUENCE OF PRE-SOWING SEED PRIMING AND PACKAGING MATERIALS ON THE QUALITY OF SESAME (Sesamum indicum L.) SEEDS (Applied Biological Research, 2023)
The aim of this study was to assess the effect of seed priming on seed quality  of freshly harvested sesame seeds stored in different packaging materials.  During 2017-2018 and 2018-2019 different pre-sowing seed priming  were packed in aluminum foils, plastic packets, brown paper packets and  clothbags; andstoredunder ambient condition to monitor the deterioration  pattern of seed quality during 2018-19 and 2019-2020. Germination (%),  vigour index, electrical conductivity and α-amylase activity were evaluated at 2 months interval up to 8 months of storage. The results showed that among the packaging materials evaluated aluminum foil can be used for  longer period witleast deterioration. Among the treatments, polyethylene  glycol (PEG) 6000 @ -0.2 MPa, followed by KNO3 @ 50 mM and KH2PO4 @ 200 mM treatments gave high quality seeds in terms of germination,  vigour index and electrical conductivity. Therefore, seed priming of sesame  seeds with polyethylene glycol (PEG) 6000 @ -0.2 MPa may be done to produce high quality seeds which can be safely stored in aluminum foil.
Keywords: Packaging material; priming; sesame; storage